Legal Certainty in out-of-Court Dispute Resolution: Evaluation of Mediation and Arbitration Mechanisms - Mambu, Joupy G.Z (PT. Anagata Sembagi Education, 2026)
Out-of-court dispute resolution through mediation and arbitration has become increasingly preferred due to its efficiency, speed, and non-adversarial nature, yet the effectiveness of these mechanisms critically depends on the legal certainty of enforcing settlement results. This normative juridical research analyzes the regulatory framework governing the enforcement of mediation settlement agreements and arbitration awards, as well as the challenges in practice. The findings reveal three major issues that undermine legal certainty: a legal vacuum regarding the executorial authority of mediation settlements, ambiguity concerning the legal status of settlement outcomes, and normative contradictions between the principle of finality in non-litigation dispute resolution and judicial control. These issues prevent mediation and arbitration from fully guaranteeing finality, legal protection, and access to justice for disputing parties. Legal reform is therefore required to ensure automatic executorial power over mediation and arbitration outcomes and to harmonize regulatory norms to minimize excessive judicial intervention, enabling mediation and arbitration to function as independent and equivalent dispute-resolution forums that provide optimal legal certainty.